2002
DOI: 10.1128/mcb.22.15.5281-5295.2002
|View full text |Cite
|
Sign up to set email alerts
|

PIN1 Is an E2F Target Gene Essential for Neu/Ras-Induced Transformation of Mammary Epithelial Cells

Abstract: Oncogenes Neu/HER2/ErbB2 and Ras can induce mammary tumorigenesis via upregulation of cyclin D1. One major regulatory mechanism in these oncogenic signaling pathways is phosphorylation of serines or threonines preceding proline (pSer/Thr-Pro). Interestingly, the pSer/Thr-Pro motifs in proteins exist in two completely distinct cis and trans conformations, whose conversion is catalyzed specifically by the essential prolyl isomerase Pin1. By isomerizing pSer/Thr-Pro bonds, Pin1 can regulate the conformation and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
294
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(312 citation statements)
references
References 59 publications
(133 reference statements)
15
294
0
3
Order By: Relevance
“…One mechanism involves E2F-induced activation of genes whose protein products positively regulate p53 stability and transcriptional activity; this group is constantly growing and presently includes ARF, ATM, Chk2 and PIN1. [15][16][17][30][31][32][33][34][35][36] After its stabilization and activation, p53 can elicit a number of different cellular responses including, most notably, growth arrest and apoptosis. The E2F-regulated genes listed above, while contributing to p53 activation, do not explain how E2F1 directs p53 to favor apoptosis over growth arrest.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism involves E2F-induced activation of genes whose protein products positively regulate p53 stability and transcriptional activity; this group is constantly growing and presently includes ARF, ATM, Chk2 and PIN1. [15][16][17][30][31][32][33][34][35][36] After its stabilization and activation, p53 can elicit a number of different cellular responses including, most notably, growth arrest and apoptosis. The E2F-regulated genes listed above, while contributing to p53 activation, do not explain how E2F1 directs p53 to favor apoptosis over growth arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Pin1 is also controlled by E2F1 and induced during cell cycle progression. 76,77 Moreover, phosphorylation events regulate both its nuclear localization and substrate binding capability (reviewed in Wulf et al 59 ), while recently its ubiquitin-mediated degradation has been found to be inhibited by mitotic signals through Polo-like Kinase1 (Plk1). 78 Plk1 is overexpressed in many tumors and this may contribute to the increased levels of Pin1 observed in several cancers.…”
Section: The Prolyl Isomerase Pin1mentioning
confidence: 99%
“…Recent studies have demonstrated that Pin1 increased the transcription level of several oncogenes including cyclin D1 and c-myc as well as conferred anchorage-independent cell growth to normal mammary epithelial cells (16,34). Breast cancer for example, Pin1 protein overexpression can lead to cyclin D1 elevation and transformation of breast epithelial cells (16,34).…”
Section: Discussionmentioning
confidence: 99%
“…By using an antisense approach, Ryo et al, showed that down-regulation of Pin1 in HeLa cells led to a decrease in ß-catenin levels (15). In Pin1 knockout mice, lower ß-catenin levels were found in all tissues compared to those of wild-type mice (15,34). In addition, Pin1 has been demonstrated to bind directly to phosphorylated ß-catenin at pT246P motif in vitro and in vivo and block the interaction between ß-catenin and APC (15,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation